Comparison Study Between Laparoscopic Radical Prostatectomy versus Robotic Radical Prostatectomy in Patient with TUR-P History - Moamar Andar Roamare Siregar; Chaidir Arif Mochtar; Rainy Umbas; Agus Rizal Hamid (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: The number of men with benign prostate hyperplasia undergoing transurethral resection of prostate (TURP) with the subsequent development of prostate cancer has been increasing. This study aimed to compare the surgical, oncological, and functional outcomes of robotic and laparoscopic radical prostatectomy techniques in patients with the history of TURP.Methods: Literature search of electronic databases was performed through Pubmed, Science Direct, SCOPUS, and CENTRAL databases. Cochrane Risk of Bias Tool was then employed to assess the risk of bias in each study. Grey literature was also searched from sources such as Cancer Care Ontario and conference abstracts. Critical appraisals of included studies were conducted using the Newcastle-Ottawa Scale.Results: The searches located 1258 citations, but only 11 studies were included in the final selection. Most studies had a good methodological quality based on the Ottawa Scale. The mean age of samples was varied among each study from 61.8 to 70.8 years. The TURP history significantly affects biochemical recurrences (OR 2.29, 95% CI 1.14–4.59), intraoperative blood loss (MD 57 ml; 95% CI 6–108 m), prolonged operative duration (MD 20 minutes; 95% CI 3–37 minutes), and surgical complications (OR 2.54, 95% CI 1.79–3.60) following radical prostatectomy for prostate cancer. In the subgroup analysis, only prolonged operative duration and surgical complications were significant both in laparoscopic and robotic radical prostatectomy. There was no association between the TURP history and the positive surgical margin rate in total and subgroup analyses. Conclusions: The previous TURP history affects the outcomes of patients who underwent radical prostatectomy, either laparoscopic or robotic.